Characterization of hydro-meteorological drought in Nepal Himalaya: a case of Karnali River Basin - Khatiwada, K.R.; Pandey, Vishnu Prasad (Elsevier, 2019)
Himalayan river basin is marked by a complex topography with limited observational data. In the context of increasing extreme events, this study aims to characterize drought events in the Karnali River Basin (KRB). Firstly, historical data for 34-years (1981–2014) from ten different stations were analyzed to compute following drought indices: Standardized Precipitation Index (SPI), Standardized Precipitation Evapotranspiration Index (SPEI), Reconnaissance Drought Index (RDI), Self-Calibrated Palmer Drought Severity Index (sc-PDSI), Standardized Streamflow Index (SFI), and Palmer Hydrological Drought Severity Index (PHDI). Among them, SPI is able to capture the drought duration and intensity fairly well with the others. Secondly, SPI was used to analyse the drought of the entire basin. The SPI analysis showed occurrence of major drought events in the recent years: 1984–85, 1987–88, 1992–93, 1994–95, 2004–09, and 2012. The winter drought of 1999, 2006, 2008–09 were widespread and the monsoon drought is increasing its frequency. No particular pattern of drought was observed from the historical data; however, yield sensitivity index revealed that precipitation pattern and anomaly is influencing crop yield in the area. Being the first study revealing prevalence of the drought in KRB, it can provide a basis for prioritizing interventions focused on drought management in the region.